Analisis Perbandingan Perilaku Mahasiswa Kesehatan Di Kota Medan Dalam Pencegahan Covid 19 - roni gunawan; Alfiyansyah Hasibuan (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Introduction: The Corona Virus Disease 19 (COVID-19) is a disease that has a major impact on public health in 2020. This epidemic has an impact on the development of the digitalization system in every aspect of life. Information that is widely disseminated on social media becomes very important to be accessed by all parties, including those who are familiar with health information, namely health students. Health students with various majors have their own characteristics that in fact affect their behavior in preventing Covid 19. Method: The research method used is a comparative analytical survey method, which compares the behavior of preventing Covid 19 in 4 student departments in the city of Medan, namely Public Health, Pharmacy, Nursing. and Physiotherapy. The total number of respondents is 80 people where each department is 20 people. Data analysis used the Kruskall Wallis test with the Post Hoc test using the Mann Whitney test. Result:. Based on the analysis of the behavioral aspects tested, there are differences in the four majors, namely the Action variable only. Then based on post hoc analysis, the difference between these actions occurred in the Department of Public Health and Pharmacy with a p value of 0.041. Then the difference in Action also occurs in the Department of Public Health and the Department of Nursing with a p value of 0.010. Then the difference in action also occurred in the Department of Public Health and the Department of Physiotherapy with a p value of 0.001